The Economic Value of Environmental Services in the Karst Area of Jatijajar Village - Rasyid Wisnuaji; Pahrul Fauzi (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2022)
Jatijajar Village is included in the Gombong karst area based on the Minister of Energy and Mineral Resources Decree No. 3043 K/40/MEM/2014 and was confirmed by the Kebumen Regency Regional Regulation No. 23 of 2012 concerning RTRW of Kebumen Regency. It has the potential value of environmental and ecological services both in the karst area itself and in the non-karst area which is used as a buffer zone. The underground river system provides benefits to the environment around the karst area and even the community as a provider of clean water needs that are perennial/flowing throughout the season. The contingent valuation method is used as an approach in this research. Primary data obtained from field research is used as the main data. The analysis of environmental services used is the willingness to pay technique of individuals for environmental services or resources. Natural resources in the Karst Gombong area of Jatijajar Village have characteristics in the form of direct use, the value of water resources for lowland rice farming and Water resources from underground rivers in the karst area is 15 springs. The total economic value of the potential use of existing resources in the Gombong Karst Gombong area of Jatijajar Village is IDR 87,616,789,519 in one year. The magnitude of this value is the value of natural and environmental resources from the direct use of the availability of natural resources to the community. These values will be lost if the karst area is damaged either from mining activities or changes in environmental functions.Keywords: Karst; Economic Valuation; Natural resource and environmental economics; Total Economic Value.